Design, commissioning and first measurements at the LEETECH spectrometer - D. Attie; S. Barsuk; O. Bezshyyko; L. Burmistrov; A. Chaus; P. Colas; O. Fedorchuk; L. Golinka-Bezshyyko; I. Kadenko; V. Krylov; V. Kubytskyi; R. Lopez; et al. (Ядерна фізика та енергетика)
The LEETECH (Low Energy Electron TECHnique) electron test beam facility has been designed and manufactured at Laboratoire de l’Accelerateur Lineaire (Orsay, France). Energy of electron beam can vary from 100 keV to 5 MeV. Two measurement sessions with application of the diamond sensor and the Micromegas/InGrid tracking module characterization were performed. Complete facility design with the Geant4 simulation, mechanical design, implementation of remote control and readout system is presented. An option to generate the electron bunches including a few particles only is confirmed, the obtained results are in rather good agreement with the corresponding simulation within uncertainty. Main results with the preliminary analysis from the Micromegas/InGrid measurement session are also presented.